Fast purification method of functional LPMOs from Streptomyces ambofaciens by affinity adsorption. (7th August 2017) - Valenzuela, Susana V.; Ferreres, Guillem; Margalef, Gerard; Pastor, F.I. Javier
Abstract: A simple purification method by affinity adsorption was developed to obtain functional lytic polysaccharide monooxygenases (LPMOs). The system allows the successful purification to homogeneity of the most characterized bacterial LPMO, CBP21 from Serratia marcescens, and two LPMOs from Streptomyces ambofaciens, which have not been previously characterized. The first of these new LPMOs, named SamLPMO10B is a small enzyme (15 kDa) belonging to family 10 of auxiliary activities (AA10), showing activity on β-chitin. The second LPMO, SamLPMO10C (34.7 kDa), is a bimodular enzyme comprised of an AA10 catalytic module and a carbohydrate binding module of family CBM2. SamLPMO10C shows activity on cellulosic substrates, including agricultural fiber paper pulps. The methodology developed simplifies the purification process to a binding-elution protocol with low-grade polysaccharides including Avicel. The strategy can be a cheap, simple and fast solution for the purification of LPMOs for industrial applications, leaving out periplasmic fractionation from recombinant strains therefore, with reduction of time and costs compared to conventional processes. The activity of SamLPMO10C expands the potential of the high valued LPMOs in lignocellulosic biomass valorization, reaffirming their promising role in cellulose deconstruction. Graphical abstract: Highlights: New method for LPMOs purification was developed. Purification to homogeneity by binding and elution from polysaccharides. Identification of two new LPMOs from Streptomyces ambofaciens . LPMO SamAA10C produces oxidized cellooligosaccharides from agricultural fibres paper pulp.